Governance matters: an ecological association between governance and child mortality - Lin, Ro-Ting (Oxford University Press, 2014)
BACKGROUND: Governance of a country may have widespread effects on the health of its population, yet little is known about the effect of governance on child mortality in a country that is undergoing urbanization, economic development, and disease control. METHODS: We obtained indicators of six dimensions of governance (perceptions of voice and accountability, political stability and absence of violence, government effectiveness, regulatory quality, rule of law, and control of corruption) and national under-5 mortality rates for 149 countries between 1996 and 2010. We applied a semi-parametric generalized additive mixed model to examine associations after controlling for the effects of development factors (urbanization level and economy), disease control factors (hygienic conditions and vaccination rates), health expenditures, air quality, and time. RESULTS: Governance, development, and disease control showed clear inverse relations with the under-5 mortality rate (p<0.001). Per unit increases in governance, development, and disease control factors, the child mortality rate had a 0.901-, 0.823-, and 0.922-fold decrease, respectively, at fixed levels of the other two factors. CONCLUSIONS: In the effort to reduce the global under-5 mortality rate, addressing a country's need for better governance is as important as improvements in development and disease control.